Comparison of Enamel Morphologic Characteristics after Conditioning with Various Combinations of Acid Etchant and Er:YAG Laser in Bonding and Rebonding Procedures: A SEM Analysis - Mohammad Sadegh Ahmad Akhoundi; Ardavan Etemadi; Maryam Nasiri; Elahe Soltanmohamadi Borujeni (Tehran University of Medical Sciences, 2017)
Objectives: Many studies have evaluated re-etched enamel by using scanning electron microscopy (SEM); however, there is no evidence regarding the use of Erbium-doped yttrium aluminium garnet (Er:YAG) laser at primary and secondary bonding instead of acid etching with regards to enamel surface changes. The purpose of the present study was to determine that whether or not the methods of primary and secondary enamel preparation affect enamel characteristics after rebonding, by using SEM analysis. Materials and Methods: Twelve freshly extracted premolars were divided into 4 groups. The samples in each group were conditioned by acid etchant or Er:YAG laser at primary conditioning, according to the instructions. Afterwards, they were bonded with orthodontic brackets. After debonding, the samples were prepared for second conditioning. Also, two samples were conditioned only once with acid etchant or laser, to compare enamel morphology changes with those after re-etching. Finally, buccal enamel surfaces were evaluated using SEM. Results: Enamel etching patterns were observed in the samples which had been acid-conditioned at first or at both conditionings. The samples irradiated by Er:YAG laser showed amorphous and irregular surfaces, with no signs of typical etching patterns. A large deep gap was seen in one of the samples irradiated with laser at primary and secondary conditionings, which might have penetrated the underling layers of enamel and dentin. Conclusions: Enamel surface preparation with Er:YAG laser produces irregular and indistinct morphologic changes, completely different from those produced after acid etching at both conditioning and reconditioning. Therefore, it is recommended to use this laser with caution to avoid permanent enamel damage.